Talk or Dare Card Media as an Innovative Linguistic Tool for Enhancing Arabic Speaking Performance - Silma Silma; rosmiati rosmiati; Ruslan Ruslan (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
peaking skills are one of the essential competencies in Arabic language learning, yet many students encounter difficulties due to limited vocabulary, fear of making mistakes, and lack of self-confidence. This study aims to: (1) implement the Talk or Dare card media in Arabic language learning, (2) identify its impact on students’ speaking skills, and (3) examine the supporting and inhibiting factors in Arabic speaking performance. The research employed Classroom Action Research (CAR), conducted in two cycles, each consisting of four stages: Planning, Action, Observation, and Reflection. The research subjects were 40 students of class VIII.7. Data were collected through observation, interviews, and speaking skill tests. The results showed a significant improvement in students’ speaking skills after the implementation of the Talk or Dare card media. The average score increased from 63.37 in the pre-cycle to 74.47 in cycle I, and further improved to 86.17 in cycle II. The percentage of learning mastery rose from 25% to 57.5%, and then to 82.5%. This media proved effective in creating an enjoyable and interactive learning atmosphere, while also boosting students’ confidence in speaking. Supporting factors included student motivation, engaging teaching methods, and teacher support, while inhibiting factors were limited vocabulary and shyness in speaking before peers. The contribution of this study lies in affirming the effectiveness of linguistically based innovative media in significantly enhancing Arabic speaking skills.